Voice without influence: small- and medium-sized enterprises in childcare. (2nd October 2017) - Gautam, Amrita; Markey, Raymond
ABSTRACT: There is abundant research on employee voice, but most focuses on large organisations rather than small organisations, which limits the voice literature. With the aim of addressing this limitation, this study explores different factors affecting voice and its outcomes in small- and medium-sized enterprises (SMEs), utilising semi-structured interviews in three childcare centres in Sydney, Australia. While past literature assumed that employee voice practices implemented in large organisations could be practiced in SMEs creating similar outcomes, the findings of this study indicate that the unitary stance of employees and managers/supervisors in SMEs regarding the definition and perception of voice challenges the practice of voice as indicated by the literature. It suggests that further exploring voice in SMEs would bridge an important gap in voice literature.